2018
DOI: 10.17576/pengurusan-2018-52-17
|View full text |Cite
|
Sign up to set email alerts
|

Pembangunan dan Penilaian Model Hasrat Mengguna Aplikasi Mudah Alih Penasihatan Penyakit Tanaman Lada Hitam

Abstract: ABSTRAK Kajian hasrat mengguna aplikasi mudah alih dalam domain pertanian masih kurang diterokai. Penggunaan m-Pertanian seperti aplikasi memberi faedah apabila menerima dan mengguna aplikasi tersebut. Tujuan kajian ini adalah untuk membangun sebuah model Tingkah laku hasrat mengguna (HM) aplikasi mudah alih penasihatan penyakit untuk tanaman lada hitam (m-Naslada), mengesah model HM serta membangun prototaip m-Naslada berdasarkan beberapa faktor daripada model HM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In order to offer advice on common diseases and a pest to the pepper farmers, as well as educating them with minimum cost possible, a mobile app for pepper advisory was developed. As most farmers were using Android-based smartphone [24], the advisory app, known as Dr.LADA were developed with Android Studio. Android Studio is a Java-based integrated development platform for mobile apps.…”
Section: Proposed System Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…In order to offer advice on common diseases and a pest to the pepper farmers, as well as educating them with minimum cost possible, a mobile app for pepper advisory was developed. As most farmers were using Android-based smartphone [24], the advisory app, known as Dr.LADA were developed with Android Studio. Android Studio is a Java-based integrated development platform for mobile apps.…”
Section: Proposed System Architecturementioning
confidence: 99%
“…In order to know the farmer's readiness in adapting the technology, surveys conducted on these farmers [23] shown that majority of the pepper farmers in Sarawak own a smartphone. Thus, a model of intention to use a disease advisory app was developed [24].…”
Section: Introductionmentioning
confidence: 99%